Effect of optimisation variable and the role of plant extract in the synthesis of nanoparticles using plant-mediated synthesis approaches - Ahmad, Nor Monica; Mohamed, Ahmad Husaini; Hasan, Nor'Aishah; Zainal- Abidin, Nurhamimah; Nawahwi, Mohd Zaini; Mohamad Azzeme, Azzreena (Elsevier B.V., 2024)
Implementing nanoparticles (NPs) is crucial in many areas, such as agriculture, environment, food, industrial, and medical. These NPs can be produced through physical and chemical methods. Interestingly, the increasing demand for green technologies has highlighted the advantages of green-based biological methods that yield unique NPs with significant properties, including high conductivity, effective catalytic activity, high reducing potential, minimal agglomeration, less complicated procedure, less toxicity, and reduced research cost. Extracts from various plant parts can serve as natural reducing agents, stabilisers, or capping agents to the precursors during synthesis. Although numerous studies have reported the synthesis of NPs via the biological method, information on the key strategy for developing plant-mediated NPs remains scarce. In light of this research gap, this review aimed to provide a fresh perspective on the optimisation strategies and their impact on the novel preparation of plant extract-based NPs in terms of surface morphology, size, and performance in various field applications. This review also describes the roles of plant extracts as a reliable reducing and capping agent, the multiple mechanisms and factors affecting the synthesis process, including the concentration of plant extracts, metal ions, reaction temperature, and time, and a detailed discussion of various plant-based NP synthesis. Finally, the review highlights the current and potential application of green-based NPs.